Mechanisms of Apoptotic Cell Death by Stainless Steel Nanoparticle Through Reactive Oxygen Species and Caspase-3 Activities on Human Liver Cells - Almutairi, Bader; Ali, Daoud; Yaseen, Khadijah N.; Alothman, Norah S.; Alyami, Nouf; Almukhlafi, Hanouf; Alakhtani, Saad; Alarifi, Saud (Frontiers in Molecular Biosciences, 2021)
Background Nanoparticles are widely used in pharmaceutical, agriculture, food processing industries, and many other fields. However, the effect of stainless steel nanoparticles (SSNPs) remains unclear. So in this experiment, we evaluated the role SSNPs toxicity on human liver (CHANG and HuH-7) cell lines over 24 and 48 h. Methods We have analyzed the quality, shape, and size of SSNPs using X-ray diffraction (XRD), energy dispersive X-ray (EDX) scanning electron microscope (SEM), and transmission electron microscope (TEM). The cytotoxicity and cell growth were determined by using MTT and wound healing tests. Thes oxidative stress parameters were determined by measuring ROS generation and antioxidant enzymes such glutathione (GSH) and superoxide dismutase (SOD) due to SSNPs exposure on human liver cell lines over 24 and 48 h. The confirmation of the apoptotic effect of SSNPs on livers cells was determined by western blot for expression of apoptotic proteins such as Bax, bcl2, and p53 and real-time PCR for expression of apoptotic genes such as Bax, bcl2, caspase-3, and p53. Results We have observed dose and time-dependent cytotoxicity and apoptosis of SSNPs on both cells. Results showed that SSNPs induced cell toxicity, inhibited cell growth, GSH, and increased generation of intracellular ROS and SOD level at higher concentrations of SSNPs exposure in both cells. SSNPs showed apoptotic activity with upregulation of Bax, caspase-3, p53, and downregulation of bcl2 genes expression in CHANG and HuH-7 cell lines. Moreover, immunoblotting assay confirmed the apoptotic activity of SSNPs in cells. Conclusions In conclusion, these findings demonstrated that SSNPs executed toxic effects on human liver cells via activating caspase-3 activity and it induced more toxicity on HuH-7 cells than CHANG cells. Keywords: CHANG &HuH-7 cells; SSNPs; Apoptosis; Oxidative stress; RT-PCR